Pid Board : Type 5120 - Technical Description - Hps SystemTechnik
The hps Pid board (Type 5120) is a demonstration and training unit with a wide range of possible applications with the emphasis on the field of control engineering principles. The jump or rise functions of all common control circuit elements can be investtigated. Bode diagrams and locus curvers of these control circuit elements can also be determined with a additonal sine generator and the appropriate measuring instruments....